Analysis of green supply chain of coffee Lindu Biosphere reserve at Pipikoro Coffee Company - Putrawan, Sendi; Miru, Sulaeman; Asngadi, Asngadi; Syam, Syamsuddin; Zainuddin, Fatlina (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study aims to analyze green supply chain activities within the Lore Lindu Biosphere Reserve and the Pipikoro Coffee company. Observations in the reserve area reveal extensive community farming activities, including within conservation zones, yet academic studies on such practices remain limited. At Pipikoro Coffee, the researcher identified a lack of comprehensive analysis regarding the involvement of key supply chain actors—farmers, processors, and consumers—in supporting sustainability initiatives. Using a phenomenological paradigm and a qualitative descriptive approach, this research was conducted at Pipikoro Coffee in South Lolu Village, South Palu District, Palu City, involving 10 informants. Data were analyzed using triangulation techniques and the NVivo 12 Plus software. The findings indicate that Pipikoro Coffee’s green supply chain relies on five interrelated components: suppliers, manufacturers, distributors, retailers, and customers. Each component functions through inbound, operational, and outbound processes that collectively support sustainable practices. Key elements identified include farmer education, the adoption of eco-friendly roasting technology, and consumer participation in promoting sustainable local products. Overall, this study highlights the importance of deeper exploration into how green supply chain practices are implemented in biosphere reserves and local enterprises, emphasizing their role in aligning conservation goals with sustainable business operations.